2006
DOI: 10.1056/nejmoa052475
|View full text |Cite
|
Sign up to set email alerts
|

Familial Sinus Bradycardia Associated with a Mutation in the Cardiac Pacemaker Channel

Abstract: We found that sinus bradycardia in members of a large family was associated with a mutation in the gene coding for the pacemaker HCN4 ion channel. Pacemaker channels of the sinoatrial node generate spontaneous activity and mediate cyclic AMP (cAMP)-dependent autonomic modulation of the heart rate. The mutation associated with bradycardia is located near the cAMP-binding site; functional analysis found that mutant channels respond normally to cAMP but are activated at more negative voltages than are wild-type c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
277
2
7

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 358 publications
(301 citation statements)
references
References 23 publications
15
277
2
7
Order By: Relevance
“…4). To further confirm this finding we extended our analyses and investigated additional marker genes for the conduction system also by qPCR, namely Shox2, Tbx3, and Cx30.2 (Coppen et al, 1998;Hoogaars et al, 2004;Kreuzberg et al, 2005;Milanesi et al, 2006;Mommersteeg et al, 2007;Espinoza-Lewis et al, 2009). All marker genes were strongly up-regulated in Tbx5-overexpressing cells, except Cx30.2 (Figs.…”
Section: Tbx5 Overexpression In Murine Es Cells and Xenopus 2637mentioning
confidence: 62%
“…4). To further confirm this finding we extended our analyses and investigated additional marker genes for the conduction system also by qPCR, namely Shox2, Tbx3, and Cx30.2 (Coppen et al, 1998;Hoogaars et al, 2004;Kreuzberg et al, 2005;Milanesi et al, 2006;Mommersteeg et al, 2007;Espinoza-Lewis et al, 2009). All marker genes were strongly up-regulated in Tbx5-overexpressing cells, except Cx30.2 (Figs.…”
Section: Tbx5 Overexpression In Murine Es Cells and Xenopus 2637mentioning
confidence: 62%
“…38 Mutations in HCN4 have been associated with sinus node dysfunction. 39,40 The SNP rs10824026 is located on chromosome 10q22, 5-kb upstream of SYNPO2L. 18 Beqqali et al 41 identified the gene as encoding a cytoskeletal protein, which is highly expressed in the Z-disc of cardiac and skeletal muscle.…”
Section: The 4q25 Locusmentioning
confidence: 99%
“…In particular, the role of HCN channels as the dominant mechanism in heart rate regulation has repeatedly been called into question (4,23). Human genetic studies have suggested that HCN4 channels are important components of the SAN pacemaker machinery (9)(10)(11)(12). A contribution of I f to heart rate determination is further supported by the observation of a heart rate-lowering effect in both humans and rodents when I f is specifically blocked with IVA (13,14,24).…”
Section: Hhcn4 -573x Expression Eliminates Camp Sensitivity Of If Andmentioning
confidence: 99%
“…Although these biophysical properties seem to make f-channels ideal molecular targets for heart rate regulation, the contribution of the major I f -mediating cardiac isoforms HCN2 and HCN4 to SAN function remains highly controversial. Although human genetic (9)(10)(11)(12) and pharmacologic (5,13,14) studies suggest a significant role for HCN4 subunits in SAN pacemaking in humans and rodents, recent data from transgenic mouse models have challenged this view (15,16). Targeted deletion of HCN4 in adult mice was found to cause heart ratedependent sinus pauses but to have no effect on either basal or maximal heart rate or heart rate regulation (16).…”
mentioning
confidence: 99%